Five new species of Huberia (Melastomataceae) from the eastern Brazilian mountains - Thuane Bochorny; Paulo M. Gonella; Lucas N. Gonçalves; Rafael R. Völtz; Renato Goldenberg (Plant Ecology and Evolution)
Background and aims – Huberia is a genus with 37 species mostly occurring in high elevation grasslands in eastern Brazil, except for four species in the Andes of Ecuador and Peru. It belongs to tribe Pyramieae (Melastomataceae) and can be recognized by tetra- to heptamerous flowers with a campanulate or apically constricted hypanthium, white to light-pink or purple petals, and stamens bearing dorsal connective appendages. Material and methods – We describe five new species in Huberia and also provide detailed photographs, taxonomic notes, distribution maps, and conservation assessments. Key results – Huberia campostriniae, H. ciliata, H. mayarae, H. revoluta, and H. rubricalyx are taxonomically described from rocky outcrops in the states of Minas Gerais and Rio de Janeiro in eastern Brazil. We recommend that these species be classified as Critically Endangered or Data Deficient according to the IUCN Red List criteria.